The prevention of anaphylactic reactions to iodine-containing contrast agents - Salo, S. V.; Lebedieva, Y. O.; RuzhуnYu. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Anaphylactic reactions to iodine-containing contrast agents (ICA) are fairly common and potentially life-threatening. At the same time, the use of ICA is contraindicated in some patients due to the risk of serious adverse effects. One of the most important circumstances is the prevalence of using of ICA in everyday clinical practice which determine the relevance of the problem. The article presents a literature review which focuses to the problem of prevention of anaphylactic reaction to ICA in patients requiring radiodiagnostic investigations. Also shows a clinical case of the effective use of Gadovist during coronary arteries (CA) stenting in patient with coronary heart disease (CHD) and allergic reactions to ICA in a history.